Otoritas Jasa Keuangan: Suatu Kajian Terhadap Raung Lingkup Independensi Dalam Mengatur dan Mengawasi Industri Jasa Keuangan Di Indonesia - Bisdan Sigalingging (SOSEK : Jurnal Sosial dan Ekonomi, 2022)
The Financial Services Authority (OJK) was established as an independent institution with the duties, functions, and authorities to regulate, supervise, examine, and conduct investigations on all financial service institutions. In carrying out its duties, functions, and authorities, OJK is still hampered by its inconsistent independence status, starting from the interpretation of independence, making policies, related to the budget, to the selection of members of the Board of Commissioners (DK). The problem discussed is how the scope of independence itself is, whether independence is only focused on the government, or also includes other parties. This normative research concludes that OJK is not only independent from the government, but also independent from all other parties. These parties include elements of the government, budget funding, financial service industries, individuals and communities, as well as other institutions that do not have the duties, functions and authority to carry out the duties, functions and authorities of the OJK. It is hoped that the independence of the OJK in the law is formulated by providing limitations from where the OJK must be independent. OJK independence must fulfill legal certainty, namely free from all forms of regulatory capture and supervisory capture, both in the OJK Law and in carrying out its duties, functions and authorities. OJK must be affirmed that it is free from all forms of interference and forms of power such as arbitrary powers of the government, legislature, judiciary, and other powers and interventions, except for the duties, functions and authorities specified in the OJK Law.